A Credit Crunch? : A Case Study of Finland in the Aftermath of the Banking Crisis - Pazarbasioglu, Ceyla (IMF Working Papers; Working Paper ;, 1996)
This paper estimates a disequilibrium model of credit supply and demand to evaluate whether there was a credit crunch in Finland following the banking crisis of 1991-92. Empirical analysis suggests that the marked reduction in bank lending was mainly in reaction to a cyclical decline in credit demand, likely exacerbated by the high level of indebtedness of the borrowers. It also appears that banks became less willing to supply credit during periods associated with a deterioration in asset quality, and reduced profits due to declining regulatory protection from competition, and a need to increase capital adequacy levels.